Pendidikan berkelanjutan nonformal bagi kepala ruangan di rumah sakit X di Jakarta - Eti Masiyati; Hanny Handiyani; Nurdiana Nurdiana (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Continuing nurse education among head nurses as a factor of health care quality at hospital X in JakartaBackground: The head of the room as a line manager nurse plays an important role in the Health and Nursing Service which is rapidly changing. The head of the room in carrying out his role and function is inseparable from the management process, including applying attention to material resources and human resources of nursing, so the head of the room must have supporting competencies in carrying out their duties.Purpose: Data obtained through interviews, observations, Focus Group Discussion (FGD) and surveys in the form of questionnaires. Data analysis is intended to diagnose problems and formulate solutions.Results: The formulation of the problem obtained is not yet optimal continuing education programs for the head of the room. Problem solving in the form of activities using the action research approach that is by applying curriculum-based training methods that are prepared in accordance with the competency standards of the head of the room. The action research was carried out within 3 months, from October to December 2019. The results of this action research showed an increase in knowledge from the head of the room. Evaluation through pre and post test about the training material that has been given. The mean score of pre and post test participants increased from an average of 53.88 to 80.36 or an increase of 26.48 points.Conclusion: The continuing education program for a head nurse has not been realized and in solving problems in the form of activities using the action research approach method has not been optimally implemented and arranged in accordance with the competency standards of the head of the room. It is recommended that the hospital management be able to evaluate nursing resources, especially for each a head nurse and provide opportunities to participate in continuing education and can improve quality patient care according to current technological advances. Keywords: Continuing education; Nurse manager; Competence, Head Nurse; TrainingPendahuluan: Kepala ruangan sebagai perawat manajer lini berperan penting dalam Pelayanan Kesehatan dan Keperawatan yang sangat cepat mengalami perubahan. Kepala ruangan dalam menjalankan peran dan fungsinya tidak terlepas dari proses manajemen, termasuk menerapkan perhatian kepada sumber daya material maupun sumber daya manusia keperawatan, sehingga kepala ruangan harus memiliki kompetensi yang mendukung dalam melaksanakan tugasnya.Tujuan: Mengidentifikasi penerapan fungsi manajemen sumber daya manusia di bagian keperawatanMetode: Data diperoleh melalui wawancara, observasi, Focus Group Discussion (FGD) dan Survei dalam bentuk kuesioner. Analisis data lebih ditujukan untuk mendiagnosa masalah dan merumuskan metode pemecahannya.Hasil: Belum optimalnya program pendidikan berkelanjutan bagi kepala ruangan. Penyelesaian masalah berupa Kegiatan dengan menggunakan metode pendekatan action research yaitu dengan menerapkan metode pelatihan berbasis kurikulum yang disusun sesuai dengan standar kompetensi kepala ruangan. Action research ini dilaksanakan dalam waktu 3 bulan yaitu pada bulan Oktober sampai Desember 2019. Hasil dari action research ini menunjukkan peningkatan pengetahuan dari kepala ruangan. Evaluasi melalui pre dan post test tentang materi pelatihan yang sudah diberikan. Nilai rata-rata pre dan post test peserta meningkat dari rata-rata 53.88 menjadi 80.36 atau meningkat 26.48 poin.Simpulan: Program pendidikan berkelanjutan bagi kepala ruangan belum terealisasi dan dalam penyelesaian masalah berupa kegiatan dengan menggunakan metode pendekatan action research belum optimal diterapkan dan disusun sesuai dengan standar kompetensi kepala ruangan. Disarankan kepada Manajemen rumah sakit supaya dapat mengevaluasi sumber daya keperawatan khususnya pada setiap kepala ruangan dan memberikan kesempatan untuk mengikuti pendidikan berkelanjutan dan dapat meningkatkan pelayanan pasien yang berkualitas sesuai kemajuan teknologi saat ini.